The contributions regarding to the behavior of bearings in wind turbines - Panait, Paula-Gabriela; Panaitescu, Mariana; Scupi, Alexandru-Andrei; Panaitescu, Fanel-Viorel (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
With the growth of the wind industry in the world and the commissioning of turbines with powers higher than 1 MW, higher loads and increased stresses have a strong effect on the durability of the bearings that equip the main shaft and the kinematic transmission of wind turbine gears. As a result, the wind industry is demanding greater durability of the bearings that equip the main shaft and the kinematic transmission with gears, and manufacturers are striving to come up with solutions for these requirements. The novelty in this work consists in the identification of some solutions, as well as improvements of the existing solutions for the construction of some mechanical systems for the existing wind turbines. We present below some constructive bearing solutions that are effective in the wind turbine industry. The research in the paper consists of: stress analysis of the load- bearing structure for the axial radial bearing with straight rollers with single ring, some aspects about lubrication of blade bearing in wind turbine and defects in blade bearings.